The ecology and evolution of constructed ecosystems as green infrastructure - Lundholm, Jeremy (Frontiers in Ecology and Evolution, 2015)
Green infrastructure consists of ecosystems that provide valuable services to urban areas. Constructed ecosystems, including green roofs, bioretention systems, constructed wetlands and bioreactors are artificial, custom-built components of green infrastructure that are becoming more common in cities. Small size, strong spatial boundaries, ecological novelty and the role of human design characterize all constructed ecosystems, influencing their functions and interactions with other urban ecosystems. Here I outline the relevance of ecology and evolution in understanding the functioning of constructed ecosystems. In turn, a research focus on the distinctive aspects of constructed ecosystems can contribute to fundamental science.